PENGARUH PENEMPATAN PRODUK DAN KESESUAIAN IKLAN PADA MINAT BELI YANG DIMODERASI SIKAP MEREK DI ADVERGAMES - Gultom, Theresia Mannuela; Kriestian NAN, Albert (Benefit, 2016)
This study was conducted to determine the influence of Product Placement and Congruity Ads toward buying interest which is moderated by consumersâ attitude on âadvergamesâ brand. The participant of this study was 100 students of Satya Wacana Christian University, which consist of 87 male students and 13 female students. All of the participants have ever played âPES 2016â game on their mobile games application. The sampling technique was purposive sampling, with questionnaire as the data collection method. The analysis used in this study was regression analysis interaction. The result showed that there was no moderation effect of product placement and congruity ads toward purchase intention, twotypes of products in the context of the game.